Analysis of Spiral Pump Discharge Based on Simulation of Fluid Flow in Hoses - Luntungan, Hengky; Tangkuman, Stenly; Gede, I Nyoman (Universitas Sanata Dharma, 2023)
One of the uses renewable energy is the use of a spiral pump with a water wheel as the driving force. Spiral pumps are classified as environmentally friendly technology because they do not require electricity or fuel. The spiral pump consists of two main parts, namely the water wheel and the hose that is wrapped around both sides of the water wheel.The aim of this research is to analyze the water discharge of a spiral pump based on fluid flow simulation in the hose. This research utilizes advances in computational fluid dynamic (CFD) simulation methods using software.The determination method proposed in this research has been applied to a waterwheel model with a diameter of 1.2 m and a width of 0.6 m. For hoses, diameters of ½, ¾, 1, 1½, and 2 inches are determined, while the river flow speed is 0.9 m/s. For a hose diameter of 2 inches, the initial flow velocity in the hose is 0.38 m/s and the final velocity at the hose outlet is 0.452 m/s. The largest pump discharge was obtained at a hose diameter of 2.0 inches, namely 0.00183 m3/s.